THE INFLUENCE OF PRODUCT INNOVATION AND SERVICE LEVEL AGREEMENTS ON B2B CUSTOMER SATISFACTION IN FORMING LOYALTY TO TELECOMMUNICATIONS PRODUCTS - Irawati Nawawi; Derriawan Derriawan; Lola Fitria Sari (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
The objectives of this study are to analyze the influence of product innovation and service level agreements (SLA) on B2B customer satisfaction in shaping loyalty toward telecommunications products. Using a quantitative approach, data were collected through surveys of customers of PT SME, with a total of 240 respondents representing companies from various industries. The analysis was conducted using Structural Equation Modeling (SEM) to examine the relationships between variables. The findings indicate that product innovation has a positive and significant impact on customer satisfaction, ultimately enhancing customer loyalty. Furthermore, service level agreements also positively affect both customer satisfaction and loyalty, demonstrating that the clarity and consistency of SLA contribute to maintaining customer trust. The implications of this study highlight the importance of continuous product innovation strategies and the improvement of service standards in the telecommunications industry to enhance customer retention and business competitiveness.